Assessment of Gender Balanced Policies across Companies - Šrámová, Michaela; Křečková Kroupová, Zuzana, 1972-; Volfová, Jitka, 1982-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The thesis aims to analyze the representation of women in the top management within companies in the Czech Republic and companies' approach towards gender diversity. Theoretical background is provided as an introduction to the topic. Terms leadership and leadership styles are defined. The thesis follows with gender leadership specifics and typical characteristics for the Czech Republic. The research part is based on the interviews with HR representatives conducted in five chosen companies. Typical managerial trajectory and gender diversity management are the key areas of the interviewed questions. The results picture a typical managerial trajectory with the emphasis on women. The thesis presents the companies' approach to the gender management and introduces activities which companies do in order to increase the number of women in their decision-making positions. Author's recommendations to the companies is included.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses